Enhanced Electrochemical Property of Li1.2−xNaxMn0.54Ni0.13Co0.13O2 Cathode Material for the New Optoelectronic Devices - Gao, Yumei; Hui, Yuchong; Yin, Hang (Frontiers in Physics, 2021)
The Li-rich Mn-based oxide cathode material Li1.2Mn0.54Ni0.13Co0.13O2 has been extensive studied for the new optoelectronic devices. To improve and enhance the electrochemical performance, Sodium doping is one of effective approaches. In this work, based on the density functional theory of the first-principles, the conductivity and potential energy of Li1.2-xNaxMn0.54Ni0.13Co0.13O2 were simulated with Materials studio, Nanodcal and Matlab. The results of the band gap, partial density of states, formation energy of lithiation, electron density difference and potential energy of electrons showed that Li1.2-xNaxMn0.54Ni0.13Co0.13O2 has a better conductivity when the Sodium doping amount x = 0.10 mol. The potential maps of Li1.2-xNaxMn0.54Ni0.13Co0.13O2 obtained in Matlab demonstrated that Sodium doping can reduce the potential well and enhance the rate capability. The analysis about calculations agreed with the experimental result of ChaofanYang’s group. This method could provide a great possibility for the investigation on the application of the new optoelectronic devices. Also, our findings could give some theoretical guidance for the subsequent electrochemical performance study on doping in the field of lithium-ion battery.